HUBUNGAN JARAK KEHAMILAN DAN PERDARAHAN POST PARTUM DENGAN RETENSIO PLASENTA - Sunirah, Sunirah (JURNAL KESEHATAN TERAPAN, 2021)
Placental retention is whether or not the placenta is expelled until or more than 30 minutes after the baby is born. Most placental separation disorders are caused by impaired uterine contractions. Objective: to determine the relationship between postpartum hemorrhage and retained placenta. The design of this study is an analytical study with a cross sectional method approach, this study uses secondary data with a population of 955 mothers who gave birth and the number of samples taken from simple random sampling, namely simple random sampling with a sample of 90 people. Respondents who experienced Placental Retention as many as 7 respondents (7.4) fewer than those who experienced Placental Retention 87 respondents (92.6%). Respondents with shorter pregnancy intervals were 13 respondents (86.7%), compared to 74 respondents (93.7%). Based on bivariate analysis with Chi-Square test, it shows a value of 0.169 <0.05, this means that there is a relationship. Respondents who experienced postpartum hemorrhage were 9 respondents (8.3%), compared to respondents who did not experience postpartum hemorrhage as many as 78 respondents (91.8%). meaning. The conclusion of this study is that there is a significant relationship between Pregnancy Distance and Postpartum Bleeding with the incidence of retained placenta. Keywords: Pregnancy Distance, Post Partum Bleeding, Placenta Retentio